GENETIC VARIABILITY IN MUTANT CONFECTIONARY SUNFLOWER (Helianthus annuus L.) - K. SAI PHANINDRA (The Journal of Research ANGRAU, 2023)
Genetic variability was induced in confectionary sunflower (Helianthus annuus L.) genotypes viz., EC 625693, EC 318761 and SCG 62 with sodium azide (NaN3) at concentrations of 100 ppm, 200 ppm and 300 ppm in distilled water for four hours along with control, respectively. The analysis of variances revealed significant differences between treatments for all ten characters under study. There was a close correspondence between GCV and PCV for all characters. High GCV, PCV, heritability and genetic advance as per cent of mean were exhibited by seed filling percentage, 100 grain weight, sugar content and seed yield plant-1. The 300 ppm showed high genetic parameters for head diameter, seed filling percentage, seed yield plant-1, 100 ppm for 100 grain weight. On the basis of per se performance, EC 625693 of 100 ppm showed positive shift in mean for seed yield plant-1 compared to control, while other genotypes showed negative response to mutagenic treatment. The material generated can be effectively improved only after attaining homogeneity among characters.